Gender and agricultural productivity: implications of the Farm Input Subsidy Program in Malawi. (31st March 2015) - Karamba, R. Wendy; Winters, Paul C.
Abstract: Alleviating gender differences in agricultural productivity is vital for poverty reduction. While numerous studies suggest that gender differences in agricultural productivity are a result of female farmers having limited access to resources, few studies investigate the role of agricultural interventions in alleviating the constraints to input use and subsequently the gender gap in productivity. This study investigates whether there are gendered gains in agricultural productivity from participating in an input subsidy program and if these gains help reduce the gender gap. Using nationally representative data that is disaggregated at the plot level, this study analyzes the large‐scale voucher‐based Farm Input Subsidy Program in Malawi. Focusing on the total value of output per hectare, relationships are identified using weighted estimators, where the weights are constructed from propensity scores, and spatial fixed effects, to address the unobservable factors that may confound the relationship between program participation and productivity. The findings suggest that participation in the program improves agricultural productivity for both male and female farmers but it does not provide disproportionate help to female famers to overcome gender disparities in agricultural productivity. This suggests that female farmers face additional constraints to productivity apart from nonlabor input use.